Cellular-membrane inspired surface modification of well aligned ZnO nanorods for chemosensing of epinephrine. Issue 5 (12th January 2017) - Mohsin, M. A.; Liu, B. D.; Zhang, X. L.; Yang, W. J.; Liu, L. S.; Jiang, X.
Abstract : Modified ZnO nanorods array to form a chemical sensor for neurotransmitters. The interspaces between the nanorods offer highly efficient immobilization of the lipid membrane containing the calixarene, which act as receptor molecule. Abstract : Neurological disorders have always triggered the interest of scientists due to the effects they have on the quality of life and the complexity they provide in their perception. Herein, we report a cellular-membrane inspired surface modification to fabricate a chemosensor for selective epinephrine detection. For this, well aligned ZnO nanorod arrays were grown on a silicon substrate using a feasible hydrothermal method and further utilized for the immobilization of a lipid membrane incorporated with calix[6]arene (in a 100 : 1 ratio) after modification with 1-octadecanthiol. Such surfaces were employed for selective epinephrine detection using electrochemical impedance spectroscopy as a transduction method. The detection process was based on the Lock & Key mechanism. A distinctive increase in charge transfer resistance was observed for epinephrine as compared to dopamine, leading to the conclusion that the sensor is sensitive and selective to epinephrine. This selectivity for epinephrine can be attributed to the slight differences in the molecular sizes of dopamine and epinephrine. Such electrochemical sensors can provide a very useful platform for the manufacturing of devices for monitoring the physiological concentrations of epinephrine.